Application of Printable ITO/PEDOT Nanocomposites as Transparent Electrodes in Optoelectronic Devices - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Conference on Lasers and Electro-Optics, 2012)
Printable transparent hybrid composites consisting of indium tin oxide (ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS)) as matrix material were developed and used as transparent electrodes in all-printed flexible electroluminescent lamps and electrochromic display
Keywords: optical devices; electro-optical devices; thin films; transparent conductive coatings